Interactions between Bacillus thuringiensis and entomophagous insects - Mohamed Samir Tawfik Abbas (Egyptian Journal of Biological Pest Control, 2020)
Abstract The interactions between insect pathogens, parasitoids, and predators have been proposed as “intraguild predation (IGP).” It occurs when two species share a host or prey (and therefore may compete) or when they engage in a trophic interaction with each other (parasitism or predation). Laboratory studies revealed that many predacious species attack and consume Bacillus thuringiensis (Bt)-infected prey with no detrimental effects on the biological parameters of the predators. However, some studies indicated adverse impact of Bt on development and biology of the predators. As for parasitoids, some studies showed no detrimental effects on the biology of the parasitoids when reared on Bt-infected hosts and others revealed negative effects on their biological aspects. Such negative effects were found to be related to Bt concentration and timing of treatment (parasitism or infection). The biological parameters of the offspring of the adult parasitoids that had emerged from infected parasitized larvae were not affected. Also, ingestion of Bt by adult parasitoids did not affect the longevity or fecundity of such parasitoids. Concerning Bt crops, a recent published report in 2019 stated that over the past 20+ years, extensive experience and insight have been gained through laboratory and field studies of non-target effects of crops producing Cry proteins. Overall, the vast majority of the studies demonstrated that the insecticidal proteins developed today do not cause adverse effects on natural enemies (parasitoids and predators) of target pests.